Tiroleses na Região de Piracicaba no final do século XIX: aspectos identitários e étnicos do Tirol no Brasil italiano - Toller, Fernando de Moraes (Universidade do Vale do Rio dos Sinos, 2025)
This research aims to analyze, through a case study, the identity aspects of Tyrolean immigrants who settled in the region of Piracicaba, State of São Paulo, more precisely in the localities of Santa Olímpia, Santana, and Charqueada. The historical timeframe focuses on the end of the 19th century, from the arrival of the first waves of Tyrolean immigrants to Brazil in the 1870s until the end of the said century. Much has been written, researched, and published about Italian and German immigration to Brazil. However, Tyrolean immigration is not widely known, and its studies are limited to a few theses, dissertations, and scarce articles on the subject, in addition to the efforts of some Tyrolean associations that attempt, in a way, to reconstruct this migratory process. There is even a tendency in historiography to study Tyroleans in Brazil sometimes as an appendage of Italian and German immigration, and sometimes as a group entirely absorbed by Italo-German immigration .With the purpose of reconstructing, as much as possible, the Tyrolean immigration process in Brazil – especially from the perspective of this ethnic group's struggle to rebuild its identity ties in a "foreign land" and to characterize its differences in relation to other ethnicities with which it was amalgamated or confused – this endeavor adopted the following methodological steps: a bibliographic survey, work with historical sources, and the development of a case study through the reconstruction of a specific life trajectory. The research demonstrated that Tyrolean immigrants were not passively absorbed or assimilated by other immigration currents, as often suggested by historiography. On the contrary, the case study revealed an active process of identity negotiation and reconstruction of community ties. It is concluded that the Tyrolean immigration experience was marked by a deliberate collective effort to sustain a distinct identity, organized around its cultural references.
Keywords: Imigração; Tiroleses; Identidade; Piracicaba; Augusto Toller; Immigration; Tyroleans; Identity; ACCNPQ::Ciências Humanas::História